P117 The impact of holding the baby following stillbirth on maternal mental health and wellbeing: findings from a national survey. (13th September 2016) - Redshaw, M; Hennegan, JM; Henderson, J
Abstract : Background: Perinatal loss is associated with short and long term consequences for mental health and wellbeing. Actions surrounding the birth and immediate postnatal care are critical in women's experience and outcomes. Care recommendations have varied over time. There has been controversy around policies recommending women do, or do not, hold their baby after stillbirth and guidelines have been modified. Despite debate on the issue, recent systematic review has revealed that evidence for the effect of holding the baby after stillbirth is limited and findings to date have been mixed. Past studies have found both positive, negative, and null effects of contact. This study aimed to compare mental health and wellbeing outcomes at three and nine months after the stillbirth between women who held or did not hold their baby, adjusting for demographic and clinical differences. Methods: Data from a postal population survey of women with a registered stillbirth in England in 2012 was analysed. 468 eligible responses were compared on primary outcomes of self-reported depression, anxiety, PTSD symptoms and relationship difficulties. Differences in demographic, clinical and care characteristics between those who had or did not hold their infant were described and adjusted for in subsequent analysis. Mental health and wellbeing outcomes were compared, and subgroup comparisons tested hypothesised moderating factors including the condition of the baby, and women's current pregnancy status. Results: Most women saw (97%) and held (84%) their baby after stillbirth. There were some demographic differences, with migrant women, women who had a multiple birth or whose pregnancy resulted from fertility treatment less likely to hold their baby. Primary outcomes will be detailed in presentation. Findings suggest a protective effect of seeing the stillborn baby, but indicate a negative impact of holding. results will be detailed carefully, as they are in contrast to qualitative study findings which describe individual women's positive feelings and satisfaction with holding their baby after stillbirth. Some evidence for proposed moderators was observed, including an effect of young gestational age and mother's pregnancy status at outcome assessment. Conclusion: This study supports concern about the impact of holding the infant after stillbirth and highlights the need for further quantitative research. The study findings add important evidence to a mixed body of literature.